Adult diagnosis of Swyer-James-MacLeod syndrome: a case report - Capela, Carlos (2011)
Swyer-James-MacLeod syndrome or unilateral hyperlucent lung syndrome is a rare entity associated with postinfectious bronchiolitis obliterans occurring in childhood. It is characterized by hypoplasia and/or agenesis of the pulmonary arteries resulting in pulmonary parenchyma hypoperfusion.